Anti-parasitic Peptides from Arthropods and their Application in Drug Therapy - Lacerda, Ariane F.; Pelegrini, Patrícia B.; de Oliveira, Daiane M.; Vasconcelos, Érico A. R.; Grossi-de-Sá, Maria F. (Frontiers in Microbiology, 2016)
Africa, Asia and Latin America are regions highly affected by endemic diseases, such as Leishmaniasis, Malaria and Chagas’ disease. They are responsible for the death of thousands of patients every year, as there is not yet a cure for them and the drugs used are inefficient against the pathogenic parasites. During the life cycle of some parasitic protozoa, insects become the most important host and disseminator of the diseases triggered by these microorganisms. As infected insects do not develop nocive symptoms, they can carry the parasites for long time inside their body, enabling their multiplication and life cycle completion. Eventually, parasites infect human beings after insects transmission through their saliva and/or feces. Hence, host insects and general arthropods, which developed a way to coexist with such parasites, are a promising source for the prospection of antiparasitic compounds, as alternative methods for the treatment of protozoa-related diseases. Among the molecules already isolated and investigated, there are proteins and peptides with high activity against parasites, able to inhibit parasite activity in different stages of development. Although studies are still taking their first steps, initial results show new perspectives on the treatment of parasitic diseases. Therefore, in this report, we describe about peptides from host insect sources with activity against the three most endemic parasites: Leishmania sp, Plasmodium sp. and Trypanosomes. Moreover, we discuss the future application insect peptides as anti-parasitic drugs and the use of non-hosts insect transcriptomes on the prospection of novel molecules for the treatment of parasitic neglected diseases.